The Effect of Multiple Glass Bead Sterilization Cycles On Cyclic Fatigue of AF BLUE S one File - Bassam Alsheekhly1 Marwah M. Adnan2 Fudhla Sadoon Al- Zubaydi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Sterilization represent an important and essential aspect, now days Most of the dentistsusually use the endodontic files for many times before they discard it, this could increase the need forreliable and fast sterilization method, but without affecting the physical properties of the endodontic files.Aim of the study: This study discusses an economic method of sterilization (glass bead) and its effecton the fracture resistance of the AF Blue S one file (Fanta) with multiple reuses of the system. Methodand materials: A total of 75 AF BLUE S one NiTi Rotary files (FANTA) #25 size with 0.04 taper and 25millimeter length, were used in this study, divided into three groups to test their cyclic fatigue resistanceafter multiple sterilization cycles. Result: The results were statically analyzed using (SPSS) software, Anovatest showed a statically high significant differences between the groups. Conclusions: Within the limitationof this study, it can be concluded that AF Blue S one file with 4 time glass bead sterilization cycle was themost fatigue resistant compared to zero and two sterilization cycle.